Community participation in rural tourism: towards a conceptual framework - Prabhakaran, Sudesh; Nair, Vikneswaran; Ramachandran, Sridar (Elsevier, 2014)
This study presents a discussion of the community participation construct, within a rural tourism perspective. The study also reviews the methodological characteristics of community participation's theory and measurement and its association to rural tourism environment. The extant literature is revisited to establish taxonomy of the methodological procedures for measuring community participation from the context of rural tourism. Hence, proposing a comprehensive conceptual framework featuring its multifaceted, intertwined and progressive nature for community participation in a rural tourism environment.